Examining the Determinants of Purchase Intention: A Survey Study on Jago Coffee Consumers in Jakarta - Satriowibowo, Nicky Alifio; Zafira, Nindya; Adiguna, Mohammad Daffa; Aras, Muhammad; Indra, Ricardo (Eduvest - Journal of Universal Studies, 2025)
The Indonesian coffee industry has experienced rapid growth, with Café on Wheels emerging as an innovative distribution model to enhance market accessibility and optimize operational efficiency. Jago Coffee, a pioneer in this sector, leverages electric vehicles (EVs) to implement dynamic customer engagement strategies. However, sustaining this business model remains challenging due to evolving consumer preferences and competitive market dynamics. This study examines the impact of Content Marketing, Electronic Word-of-Mouth (E-WOM), and Perceived Quality on Brand Equity and Purchase Intention, utilizing the Diffusion of Innovation Theory and Theory of Planned Behavior. A quantitative methodology was employed, collecting survey data from 399 active Instagram and TikTok users in Indonesia, analyzed through Structural Equation Modeling (SEM). Results indicate that Content Marketing and E-WOM significantly strengthen Brand Awareness, which subsequently drives Purchase Intention. However, Perceived Quality demonstrates no significant direct effect on Purchase Intention, suggesting that digital engagement metrics and brand perception variables exert greater influence on consumer decision-making processes. These findings underscore the critical role of social media marketing in building brand equity and stimulating purchase behavior, providing actionable strategic insights for Café on Wheels operators to enhance competitive positioning.